Fluoroscopic‐assisted laparoscopic retrieval of retained glucose sensor wire from the omentum. Issue 9 (4th August 2019) - Sang, Adam X.; Lal, Rayhan; August, Auriel; Danzer, Enrico; Buckingham, Bruce; Mueller, Claudia M.
Abstract: We describe a case in which retained wires from a continuous glucose monitor were removed from the abdominal wall and peritoneum of a 6‐year‐old boy. We highlight a concern for continuous glucose monitor use in children and discuss surgical techniques used to retrieve tiny, mobile objects from complex body cavities. Abstract : We describe a case in which retained wires from a continuous glucose monitor were removed from the abdominal wall and peritoneum of a 6‐year‐old boy. We highlight a concern for continuous glucose monitor use in children and discuss surgical techniques used to retrieve tiny, mobile objects from complex body cavities.